Impacto da estimulação elétrica neuromuscular sobre marcadores biológicos de pacientes críticos: uma revisão sistemática com metanálise - Santos, Amanda de Oliveira (2024)
Patients admitted to intensive care units commonly require intensive care and may face mobility restrictions. Neuromuscular electrical stimulation (NMES) aims to preserve or restore neuromuscular function after a period of disuse. Nonetheless, there remains a necessity to further elucidate its impact on inflammatory markers and the safety profile of this therapeutic approach. The research aims to analyze the scientific evidence regarding the impact of NMES on biomarkers in critically ill patients and to identify biomarkers that may reflect greater physiological safety in patients undergoing NMES. This is a systematic review with a meta-analysis of randomized clinical trials, following the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols) recommendations and registered in the PROSPERO database (CRD42023424413). The search was conducted through a carefully crafted search strategy in the PubMed, EMBASE, Web of Science, Scopus, Pedro, CENTRAL, Google Scholar databases, with no time or language restrictions, in addition to a manual search for references. Randomized clinical trials comparing NMES vs. control group and analyzing its impact on biological markers were included. The risk of bias assessment will be analyzed using the Cochrane Risk of Bias Tool, and evidence evaluation will be done through the GRADE classification. The search identified 10 articles reporting outcomes on biomarkers in critical patients after NMES use. The meta-analyses showed a significant decrease in the SMD% in serum levels of PCR [SMD: -0.74 (-1.09, - 0.4), p < 0.0001)] and an increase in IL-10 levels [SMD: +0.6 (0.11, 1.08), p = 0.02)] in the acute effect. The available evidence suggests that NMES is a therapeutic modality capable of inducing changes in the inflammatory profile of critical patients and maintaining physiological safety in its application.